Trends In International Migration Flows : An Extended Gravity Model Approach Over 1960-2010 - عبد مولاه، وليد; العباس، بلقاسم (المعهد العربي للتخطيط, 2015)
تطور الورقة تدفقات الهجرة الدولية باستخدام نُموذج جاذبية مُوسّع وتوزيع ثنائي سلبي ويأخذ بعين الاعتبار حالات انعدام التدفقات ما بين الدول. تُسير نتائج التقدير القائمة على إجمالي التدفقات ما بين 202 دولة وللفترة ما بين 1960 و2010 أن الدخل له أثر مُوجب وثابت. كما أن النتائج تُسير إلى الأثر المتعاظم لدور سُوق العمل في الدول المستقبلة وما يسحبه من ارتفاع في مُستوى المهارات المطلوبة كما يعكسه ارتفاع مُستوى رأس المال البشري. وبالرغم من الأثر الإيجابي لعامل اللغة المشتركة فإن دور عوامل الجوار وأثر الدولة المستعمرة يتناقص عبر الزمن. وتسير نتائج الدراسة أن العوامل السياسية والاجتماعية في الدول المستقبلة لها أثر معنوي وأقوى من أثر طبيعة النظام السياسي. كما أن سياسات دمج المهاجرين لها أثر تأثيري أكثر من سياسات تقييد الهجرة.
The paper develops an extended gravity model of migration using a Zero-Inflated Negative Binomial specification. Estimation results based on data concerning the total number of immigrants over the period (1960-2010) for 202 countries confirm the positive and almost constant effect of income. This result contrasts with the relatively rising impact of host countries’ labor markets size and requested skills as measured by the level of human capital. Contrary to common language, contiguity and ex-colonizer’s impact loosened over the estimation period. Socio-economic conditions in host countries’ impact were stronger than the political regime. Also integration policies account more than immigration restrictions in explaining migration flows.
Keywords: الهجرة الدولية -- تدفقات الهجرة الدولية -- المهاجرين -- نموذج جاذبية مُوسع